Respiratory Failure in an Adolescent with Primary Cardiac Sarcoma - Daniel Angeli; Stephen J. Angeli (Case Reports in Cardiology)
We report a case of progressive respiratory failure secondary to primary cardiac sarcoma masquerading as primary lung disease. An 18-year-old female presented to our hospital emergency department with progressive cough, dyspnea, and hemoptysis. She was treated for primary lung infection without improvement and had respiratory failure with endotracheal intubation by the third hospital day. An “intermediate” plasma brain natriuretic protein (BNP) of 216 pg/mL did not raise concerns about a heart failure diagnosis and may have delayed the correct diagnosis. Computed tomography of the chest with intravenous contrast was performed on the fifth hospital day and revealed a cardiac mass. A transthoracic echocardiogram confirmed a large left atrial mass that was obstructing mitral inflow. She was transferred to a tertiary center for emergency cardiac surgery. Primary cardiac tumors are a rare and treatable cause of heart failure in adolescent and young adult patients. Presentation can be confused with primary lung disease and must be suspected early. Plasma BNP cutoff levels used in the adult population should not be extrapolated to adolescents, as levels, both normal and abnormal, are significantly lower in this group of patients.